On the hippie trail ebook Istanbul to kathmandu and the making of a travel writer. - Steves, Rick (2025)
A  NEW YORK TIMES  BESTSELLER Stow away with Rick Steves for a glimpse into the unforgettable moments, misadventures, and memories of his 1978 journey on the legendary Hippie Trail. In the 1970s, the ultimate trip for any backpacker was the storied “Hippie Trail” from Istanbul to Kathmandu. A 23-year-old Rick Steves made the trek, and like a travel writer in training, he documented everything along the way: jumping off a moving train, making friends in Tehran, getting lost in Lahore, getting high for the first time in Herat, battling leeches in Pokhara, and much more. The experience ignited his love of travel and forever broadened his perspective on the world.   This book contains edited selections from Rick’s journal and travel photos with a 45-years-later preface and postscript reflecting on how the journey through Turkey, Iran, Afghanistan, Pakistan, India, and Nepal changed his life.   You know Rick Steves. Now discover the adventure of a lifetime that made him the travel writer he is today.